HUBUNGAN KONSEP DIRI DENGAN KEMANDIRIAN PADA ANAK USIA 5-6 TAHUN DI TK BINTANG CENDEKIA ISLAMIC LEADERSHIP PRESCHOOL AND KINDERGARTEN 2 KOTA PEKANBARU - Amalia, Yunita; Risma, Devi; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study background due to the persistence of low self-concept in children. Self-concept has an important role in determining one's behavior. A good self-concept will have a positive impact on the development of children's independence. Without being supported by an independent nature, then the children will encounter difficulties in achieving something to its full potential and they will also find it difficult to succeed. This study aimed to find out the relationship between self-concept and independence in children aged 5-6 years old at Bintang Cendikia Islamic Leadership Preschool and Kindergarten 2 in Pekanbaru. This study was quantitative study with correlation study type. Sampling technique used in this study is a sample saturated with a total sample of 42 children. The data collection techniques were used observation sheets. The data analysis techniques were used Pearson Product Moment Correlation Coefficient. Based on the hypothesis test result obtained correlation coefficient value of rxy = 0.643, it is greater than rtable = 0.304 (0,643 > 0,304) with significance level of 0,000 < 0,05. Level relationship resides in the strong category with the resulting determinant coefficient value is of 41.4% it can be seen that the concept of self-contribution of 41.4% to independence.Keyword: Independence, self-concept